Fuzzy Goal Programming Procedure to Bilevel Multiobjective Linear Fractional Programming Problems - Mahmoud A. Abo-Sinna; Ibrahim A. Baky (International Journal of Mathematics and Mathematical Sciences)
This paper presents a fuzzy goal programming (FGP) procedure for solving bilevel multiobjective linear fractional programming (BL-MOLFP) problems. It makes an extension work of Moitra and Pal (2002) and Pal et al. (2003).